Corporate Social Responsibility of Commercial Bank in Bangladesh: A Comparative Study on Nationalized and Private Banks - Islam, Md. Touhidul; Hasan, Md. Tareq (Asian Business Review, 2016)
Corporate social responsibility (CSR) refers to strategies corporations or firms conduct their business in a way that is ethical, society friendly and beneficial to community in terms of development. This research analyses the meaning of CSR based on some theories available in literature. CSR is evolving in its meaning and practice. The research discusses the role of CSR in community development. CSR movement has gathered great momentum over the past number of years and is now regarded as being at this most prevalent. CSR is presently one of the most discussed topics. The purpose of the study is to provide deep understanding about CSR benefit, accountability and show steps taken by the government. The study has been taken to observe different CSR areas of nationalized and private commercial banks and its contribution. This study found CSR practices of nationalized and private commercial banks. The study reveals that nationalized and private commercial banks are trying to swell their contribution in accordance with their performance.
Keywords: CSR; Accountability; Commercial Bank; Comparative Study